My leader, my leader’s leader, and the organization: The effects of behavioural integrity profiles on employee outcomes - Ho, Jennifer (My University, 2025)
A popular business adage asserts that the best leaders “walk the talk”—that is, effective leaders act in alignment with their words. Despite the prevalence of this maxim, organizations are rife with employees who perceive inconsistencies between their leaders’ words and actions. Existing theory and research have documented the benefits of high behavioural integrity (BI)—defined as the extent to which an observer perceives that an actor aligns their words with their actions and keeps their promises (Simons, 2002)—and the detrimental effects of low BI. Most empirical research centres around the BI of a single focal entity, specifically the immediate supervisor. Yet, multifoci perspectives assert that leaders at various hierarchical levels can simultaneously influence employees. In this thesis, I use a person-centred approach to first propose and test the notion that employees can be categorized into theoretically interpretable subgroups that are defined by distinct levels of BI directed toward three influential referents (the direct supervisor, the organization’s top leader, the organization). Second, drawing on signaling theory (Spence, 1973) and fundamental attribution error (Ross, 1977), I investigate whether the BI profiles have differential implications for employee acquiescent and quiescent silence and neglect, transmitted through trust. Study 1 uses latent profile analyses to identify a typology of five distinct BI profiles which are validated using an independent sample. Study 2 applies a time-lagged panel study to reveal support for the differential direct effects of BI profiles on quiescent silence, and the indirect effects of BI profiles on acquiescent silence transmitted via trust in direct supervisor. The BI profiles are not significantly related to neglect. My research argues for the usefulness of a person-centred approach to complement our existing variable-centred understanding of BI. Moreover, it offers insight into the pathways in which BI profiles are associated with increased or inhibited employee silence.
Keywords: Behavioural Integrity; Latent Profile Analysis; Employee Silence; Neglect; Trust